NON-INFECTIOUS COMPLICATIONS OF TOTAL HIP ARTHROPLASTY THAT ARE NOT ASSOCIATED WITH INSTABILITY OF COMPONENTS - Gayko, G.V.; Pidgaietskyi, V.M.; Torchynskyi, V.P.; Sulyma, O.M.; Haluzynskyi, O.A.; Nizalov, T.V.; Козак, Р.А. (World of Medicine and Biology, 2020)
We analysed outcomes of 369 cases in 364 patients with complications after total hip arthroplasty. In this study we focused on cases with non-infectious complications of total hip arthroplasty that are not associated with instability of components which included prosthetic head dislocations, paraarticular heterotopic ossification, periprosthetic fractures of the femur, pain in replaced joint (not associated with the instability). The effectiveness of surgical elimination of the dislocations was significantly higher compared to the closed reposition. The only efficient method to manage heterotopic ossification was its prompt removal. Open reposition, followed with metal osteosynthesis, was the only effective remedy for 100% of periprosthetic fractures. In case of vertebrogenous pain syndrome, the best results had patients with lesions of posterior column of the lumbar spine.